Bank Attribute Factors in Determining Customers’ Choice of Commercial Banks - Kattel, Manisha; Shah, Ajay Kumar (Journal of Business and Social Sciences Research, 2020)
The paper aims to identify the factors influencing customers the choice of commercial banks in Nepal. Banks mainly earn from customer deposits, so they influence customers to open bank accounts by providing different services. The study seeks to analyse the impact of different variables (reputation, service quality, financial gain, convenience, group influence, information availability, and physical facilities) on the customers’ choice of the bank. Based on descriptive and inferential research designs, the study made use of primary data collected through a structured questionnaire surveyed successfully on 150 customers having accounts in different commercial banks. Descriptive analysis shows the highest mean score in convenience, it urges banks to focus on providing easy access to their services. By using correlation and regression, the study discovered that reputation, service quality and financial gain have influenced customers to choose banks. Among the three variables measured, reputation made the strongest influence on customers' choice of the bank, whereas group influence and information availability had no impact.